In pieces [compact disc, unabridged] : a memoir - Field, Sally (Hachette Audio, 2018)
In this memoir read by the author, Sally Field tells her story for the first time, and in her own words, about a challenging and lonely childhood, the craft that helped her find her voice, and a powerful emotional legacy that shaped her journey as a daughter and a mother.